The Effect of Digital Learning Media Based on Wordwall Games on Students’ Learning Outcomes and Learning Motivation at SDN 17 Prabumulih - Popi Ulandari; Nila Kesumawati; Putri Dewi Nurhasana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
Wordwall game digital media is an interesting application, which increases motivation and learning outcomes with an active learning atmosphere in the classroom and learning while playing. The research uses the experimental method with the Posttest-Only Control Design. The research population indicates 334 people with purposive sampling, which consists of 28 students of class IIIA as the experimental class and 28 students of class IIIB as the control class. Data collection techniques used are tests and questionnaires. Based on the research results, it is concluded that there is an effect of Wordwall game-based digital learning media on students’ learning outcomes of fractional material with a sig of 0.000. There are differences in learning outcomes based on students’ learning motivation of fractional material with a sig of 0.000. There is no interaction of Wordwall game-based digital learning media on students’ learning motivation and students’ learning outcomes of fractional material with a sig of 0.788 at SDN 17 Prabumulih.